Drought, Conflict and the Use of Historical Data and Methodologies in Interdisciplinary Palaeoclimatic Research - Helen Foxhall Forbes; Mateusz Fafinski; Guy Halsall; James M. Harland; Dan Lawrence; Kelly Clarke-Neish; Lin Foxhall; Michele Abballe; Massimiliano Borroni; Ismini Lypiridou; Vicky Manolopoulou; Anastasia Nikulina; et al. (Climatic Change, 2026)
A major challenge in the interdisciplinary study of past climates is ensuring that evidence and data relating to different disciplines are analysed effectively using appropriate methodologies. In ‘Droughts and conflict during the late Roman period’, Clim. Chang 178, 2025, Norman et al. argue that historical sources support their conclusions that drought contributed causally to the ‘barbarian conspiracy’ of 367CE and to other late Roman conflicts. Although historians have developed rigorous methodologies for effective analysis and interpretation of surviving texts, the authors outline no methodologies for dealing with the textual evidence. Further, there are issues with the historical ‘conflict’ and numismatic datasets and with their interpretation. We focus on four major evidential points: 1) the ‘barbarian conspiracy’, 2) the agricultural economy; 3) the ‘conflict’ dataset and 4) the coin dataset. Historical evidence relating to drought and famine in the late Roman Empire does exist: future interdisciplinary research may indeed offer interesting observations on the relationships between drought and conflict, but the textual evidence discussed by Norman et al. does not, and cannot, support the authors’ assertions. Effective interdisciplinary research must allow all disciplines to engage on their own terms and with their own accepted standards of rigour.